2018
DOI: 10.1177/0003319718760074
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of High-Density Lipoprotein Cholesterol Are Linked to Impaired Clopidogrel-Mediated Platelet Inhibition

Abstract: Low high-density lipoprotein cholesterol (HDL-C) levels are an independent predictor of ischemic events in patients with atherosclerotic cardiovascular disease. This may in part be due to decreased clopidogrel-mediated platelet inhibition in patients with low HDL-C. We investigated the association of HDL-C with on-treatment platelet reactivity to adenosine diphosphate (ADP) in 314 patients on dual antiplatelet therapy with clopidogrel and aspirin undergoing angioplasty and stenting. Platelet P-selectin express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…In the present study it was found that HDL was a protective factor for the occurrence of CR in children with KD. Our finding was in line with a previous study of Wadowski et al suggesting that low HDL levels were linked to impaired clopidogrel-mediated platelet inhibition after angioplasty ( 35 ). Similarly, another study found that low HDL levels were associated with CR in CAD patients ( 36 ).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study it was found that HDL was a protective factor for the occurrence of CR in children with KD. Our finding was in line with a previous study of Wadowski et al suggesting that low HDL levels were linked to impaired clopidogrel-mediated platelet inhibition after angioplasty ( 35 ). Similarly, another study found that low HDL levels were associated with CR in CAD patients ( 36 ).…”
Section: Discussionsupporting
confidence: 94%
“…29 Furthermore, a previous study also suggested that in patients with low HDL-C levels, patients' platelet reactivity was enhanced. 30 Interestingly, Wadowski et al 15 found a significant association of continuous HDL-C levels with residual ADP-inducible platelet activation and aggregation. After adjusting for confounders, low HDL-C remained independently linked to increased platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study also suggested that in patients with low HDL-C levels patients platelet reactivity was enhanced [32]. Interestingly, Wadowski et al [15] found a significant association of This article is protected by copyright. All rights reserved.…”
Section: Accepted Manuscriptmentioning
confidence: 91%
See 1 more Smart Citation
“…A few reports have observed an association between the LDL-C concentration and clopidogrel; all of these studies showed that the LDL-C concentration did not affect the pharmacological effect of clopidogrel. 6,33 Wadowski et al 33 showed that a low HDL concentration increased PRU values, indicating that it is a predictor of hypo-responsiveness to clopidogrel, whereas no relationship was detected between PRU values and LDL-C/TG concentrations. Several studies have shown that a higher LDL-C concentration elevates platelet activity 34 and causes aspirin resistance.…”
Section: Discussionmentioning
confidence: 99%